2020
DOI: 10.1016/j.heliyon.2020.e05423
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and behavior regarding cigarette and water pipe smoking among Syrian undergraduates

Abstract: Background: The devastating Syrian crisis has raised concern regarding the social acceptance of smoking especially with water pipe use becoming a growing epidemic. We aim to determine the prevalence of cigarette and water pipe smoking among university students, along with identifying the addictive behavior among university students. Methods: A cross-sectional study was conducted at the Syrian Private University during World No-Tobacco Day, in Damascus, Syria during the war crisis. The survey consists of 4 sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
3
8
1
Order By: Relevance
“…Older students were more likely to be current smokers, particularly shisha smokers, while male students were more likely to be cigarette, shisha, or midwakh smokers or e-cigarette/ENDs users than female students. Compared to regional estimates, the prevalence of smoking (15.1%) among university students in the UAE in this study was lower than that reported among college students in Oman (23.5%) [28], undergraduate students in Syria (51.4%) [29], and male and female university students in Yemen (36.3% and 28.0%, respectively), Bahrain (27.0% vs. 4.2%, respectively), Tunisia (38.4% and 3.4%, respectively), Egypt (61.2% and 18.9%, respectively), Palestine (52.7% and 16.5%, respectively), and Jordan (54.3% and 11.1%, respectively) [30]. The prevalence of cigarettes (5.5%) and shisha (5.5%) smoking among university students in the UAE was far lower than that reported among UAE residents generally (37.7%) in 2018 [2], adolescents in Qatar (9.8%) [31], Libya (cigarettes: 80.2%) [32], Syria (cigarettes: 23.8%, shisha: 18.0%) [29], Jordan (cigarettes: 80.0%) [33], Saudi Arabia (cigarettes: 70.7%, shisha: 36.4-36.3%) [34,35], and Lebanon (shisha: 29.5%) [36], but slightly higher than the reported shisha smoking among university students in Bahrain (2.0%) and similar to the previously reported shisha smoking in Yemen (5.0%) [30] and among university students in Sharjah, UAE in 2005 (5.6%) [37].…”
Section: Discussioncontrasting
confidence: 87%
“…Older students were more likely to be current smokers, particularly shisha smokers, while male students were more likely to be cigarette, shisha, or midwakh smokers or e-cigarette/ENDs users than female students. Compared to regional estimates, the prevalence of smoking (15.1%) among university students in the UAE in this study was lower than that reported among college students in Oman (23.5%) [28], undergraduate students in Syria (51.4%) [29], and male and female university students in Yemen (36.3% and 28.0%, respectively), Bahrain (27.0% vs. 4.2%, respectively), Tunisia (38.4% and 3.4%, respectively), Egypt (61.2% and 18.9%, respectively), Palestine (52.7% and 16.5%, respectively), and Jordan (54.3% and 11.1%, respectively) [30]. The prevalence of cigarettes (5.5%) and shisha (5.5%) smoking among university students in the UAE was far lower than that reported among UAE residents generally (37.7%) in 2018 [2], adolescents in Qatar (9.8%) [31], Libya (cigarettes: 80.2%) [32], Syria (cigarettes: 23.8%, shisha: 18.0%) [29], Jordan (cigarettes: 80.0%) [33], Saudi Arabia (cigarettes: 70.7%, shisha: 36.4-36.3%) [34,35], and Lebanon (shisha: 29.5%) [36], but slightly higher than the reported shisha smoking among university students in Bahrain (2.0%) and similar to the previously reported shisha smoking in Yemen (5.0%) [30] and among university students in Sharjah, UAE in 2005 (5.6%) [37].…”
Section: Discussioncontrasting
confidence: 87%
“…Which he interpreted as being related to the history of chronic smoking in the male patient [7]. The results of our study may explain the noticeable increase in the smoking rate of females in society during the Syrian crisis [8].…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, cigarette smoking is associated with lower BMI (13). These are particularly concerning for Syria as one study found that among under graduate students, 51.4% smoked tobacco, 23.8% smoked cigarettes and 18.0% smoked water pipe in 2019, but this study was conducted in a private university setting (24). Another study found that smoking prevalent in Syria was 20.75% (25) while another one which was conducted in 2019 and used similar online methods to this study found that 37.9% were smokers (26).…”
Section: Discussionmentioning
confidence: 88%